2021
DOI: 10.3389/fpsyg.2021.763350
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Mindfulness Training on the Self-Awareness of Motor Symptoms in Parkinson’s Disease – A Randomized Controlled Trial

Abstract: Objective: This study aims to evaluate feasibility and effects of a newly developed mindfulness intervention tailored to specific needs of patients with Parkinson’s disease (PD).Background: The phenomenon of impaired self-awareness of motor symptoms (ISAm) in PD might be reduced by increasing patients’ mindfulness. A PD-specific mindfulness intervention has been developed and evaluated as a potential treatment option: IPSUM (“Insight into Parkinson’s Disease Symptoms by using Mindfulness”).Methods: IPSUM’s eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…In PD patients, experiencing fear can be associated with a greater risk of COVID-19 due to chronic comorbidity and is often attributed to anxiety [ 16 , 37 , 38 ]. During the pandemic, fear increases anxiety in healthy individuals and exacerbates the symptoms of individuals with previous psychiatric disorders [ 48 , 62 , 63 ]. Movement and lack of movement in patients also affect their physical, cognitive, and psychosocial health [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PD patients, experiencing fear can be associated with a greater risk of COVID-19 due to chronic comorbidity and is often attributed to anxiety [ 16 , 37 , 38 ]. During the pandemic, fear increases anxiety in healthy individuals and exacerbates the symptoms of individuals with previous psychiatric disorders [ 48 , 62 , 63 ]. Movement and lack of movement in patients also affect their physical, cognitive, and psychosocial health [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three previous MBI studies (Dissanayaka et al, 2016 ; Kwok et al, 2019 ; Pickut et al, 2015 ) also reported motor benefits, although only two (Kwok et al, 2019 ; Pickut et al, 2015 ) had significant results. Other teams sought to improve awareness of motor symptoms by using mindfulness or a novel body awareness training (BEWARE) that combined physical therapy with acceptance and commitment therapy elements (Buchwitz et al, 2021 ; Ghielen et al, 2017 ). None of these trials found significant differences with regard to their primary outcomes, although they uncovered benefits in secondary outcomes such as emotional well-being, anxiety, and cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…8 Patients with PASC who regularly practice meditation also evidence more dominant wave frequency due to a reorganization of specific cortical areas such as a hemispheric slowing and multifocal epileptiform discharges from the frontotemporal and temporoparietal head regions as well as decreased self-reported fatigue, sleeplessness, pain, and cognitive and motor dysfunction. 186,187 In one study 168 mentioned earlier in this article, participants with COVID-19 were provided a retreat and they reported positive immune-modulatory effects after 80 hours of meditation practice. The researchers concluded that findings support discrete benefits to those with COVID-19.…”
Section: Meditation For Pasc and Me/cfsmentioning
confidence: 99%
“…Patients with PASC who regularly practice meditation also evidence more dominant wave frequency due to a reorganization of specific cortical areas such as a hemispheric slowing and multifocal epileptiform discharges from the frontotemporal and temporoparietal head regions as well as decreased self-reported fatigue, sleeplessness, pain, and cognitive and motor dysfunction. 186 , 187 …”
Section: Meditation For Pasc and Me/cfsmentioning
confidence: 99%